Implementasi Metode Jigsaw dalam Mengatasi Kepasifan Siswa pada Pembelajaran PAI dan Budi Pekerti : Implementation of the Jigsaw Method in Overcoming Student Passivity in Islamic Religious Education and Character Education Learning - Nurul Fajriani; Sa’diyah Sa’diyah (Civiliza Publishing, Indonesia., 2026)
Islamic Religious Education (PAI) and Character Building (Budi Pekerti) learning is often teacher-centered, resulting in students being less active, lacking in confidence, and not optimally engaged. This study aims to describe how the jigsaw method is implemented to address student passivity in Islamic Religious Education (PAI) and Character Building (Budi Pekerti) learning at SMPN 235 Jakarta. This study used a qualitative approach with descriptive methods. Primary data sources were obtained from Islamic Religious Education (PAI) teachers and students at SMPN 235 Jakarta, while secondary data sources came from books, journals, school documents, and other supporting documentation. Data collection techniques and procedures were carried out through observation, interviews, and document studies. Data analysis used the Miles and Huberman model. The results of the study indicate that (1) Implementing the jigsaw method in Islamic Religious Education (PAI) and Character Building (Budi Pekerti) learning can reduce student passivity and improve the quality of learning. (2) This method can make students more active, confident, and easier to understand the material through group discussions and collaboration. Learning also becomes more interesting and participatory. (3) The success of this method is supported by the active role of teachers, student enthusiasm, and a conducive learning environment, while the obstacles that arise include time constraints, differences in student character, and management of group discussions.